If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-3(x-1)=292x+3)
We move all terms to the left:
7x-3(x-1)-(292x+3))=0
We multiply parentheses
7x-3x-(292x+3))+3=0
We add all the numbers together, and all the variables
4x-(292x+3))+3=0
| x(0.17)=300 | | −3c+29=8 | | 3m/7=m+4 | | 88=8(-3-2x) | | 60=90-(x+13) | | 6(2b+5)=15-7b | | 60=90-(x=13) | | 3/4(-12)+1/4(x+24)=8 | | 60=90-(x-13) | | 155-f=117 | | 2(w | | 2(w | | -6+3z=−6 | | 15-5x=21+2x | | 3/10y+15=0 | | 59=90-(x-4) | | $15-2x=3x$ | | 11x-73x+9=180 | | 262-u=9 | | -(1-7n)=-1+7n | | -78=7m-8 | | 4n2-12n-1=0 | | (12x-3)=(5x+12)=(3x+13) | | 3(t=4)=25.5 | | (12x-3)=(5x+12)=(3x+130 | | 6x-3÷5=10 | | -8-k=8(7k-1) | | 3=r+1/2 | | 5•x+3•x+2=18 | | -1(5x-2)=27 | | 32=4(a-1) | | 6-0.26f=f-3 |